Partisipasi aktif milineal dalam demokrasi: Bagaimana kaum gen z dapat mengintegrasikan nilai-nilai Pancasila dalam partisipasi aktif mereka dalam proses demokrasi, termasuk dalam pemilihan umum, kampanye sosial, dan gerakan politik - Abdillah, Rifqy; Abidin, Zaenal; Azhari, Arina Fitriya (Maliki Interdisciplinary Journal, 2024)
Democracy brings more benefits, especially in terms of elections, than negative implications. This democratic country which has an important role for a developed and prosperous country is the participation of generation z, because it can be a benchmark for concern for the country. The progress of the country depends on its people, so Generation Z is an important asset with a large population of people voting in elections, because they have good integrity and are able to apply Pancasila values.